Omega-3 Fatty Acids: Key Players in Cognitive Function and Brain Health - Wesołowska, Wiktoria; Bachoń, Emilia; Doligalska, Michalina; Stremel, Aleksandra; Leszyńska, Agnieszka; Linke, Julia; Bałoniak, Zuzanna; Kozłowska, Dominika; Bałoniak, Julia; Tuszyńska, Weronika (Journal of Education, Health and Sport, 2025)
Introduction: Omega-3 fatty acids, particularly DHA and EPA, are crucial for brain health. Modern diets, often lacking in omega-3, highlight their importance in combating cognitive decline, neurodegenerative diseases, and mental disorders. Purpose of research: This study explores the roles of omega-3 fatty acids in brain health and cognitive functions, including their mechanisms of action and potential in preventing and alleviating neurodegenerative diseases. Materials and methods: This study involves a comprehensive review of scientific literature on the impact of omega-3 fatty acids on brain health and cognitive functions. The literature search was conducted using PubMed and Google Scholar, focusing on peer-reviewed articles, clinical trials, and meta-analyses relevant to omega-3 fatty acids, brain health, cognitive functions, and mental health outcomes. Results and conclusions: Research shows that DHA and EPA supplementation can significantly improve memory and learning, especially in older individuals and those with cognitive impairments. Omega-3s also show potential in reducing the risk of neurodegenerative diseases like Alzheimer’s through their anti-inflammatory and antioxidant properties. In mental health, omega-3s can help reduce symptoms of depression and schizophrenia, although effectiveness depends on dosage and the EPA to DHA ratio. Omega-3s are essential for brain health and cognitive functions. Their supplementation, combined with cognitively stimulating activities, offers substantial benefits, especially in aging populations. Further research is needed to fully understand omega-3s’ mechanisms, optimal dosing, and their use in preventing and treating neurological disorders.